Gambaran Nilai-Nilai Kejuangan Jenderal Achmad Yani Berdasarkan Dimensi Nasionalis, Patriotik, dan Heroik pada Mahasiswa Universitas Jenderal Achmad Yani Yogyakarta - Dian Juliarti Bantam; Egi Prawita; Davit Bagus Triyantoro; Deni Santi Pertiwi; Hesty Yuliasari; Putri Pusvitasari; Edhy Tri Cahyono; Wahyu Adi Mudiparwanto; David Sulistiyantoro; Muhammad Erwan Syah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Universitas Jenderal Achmad Yani Yogyakarta (Unjaya) has values ​​internalized to the entire academic community through various programs. These are the Struggle Values ​​of General Achmad Yani (NKJA). Therefore, this study aims to identify NKJA which consists of Nationalist, Patriotic, and Heroic Dimensions in Unjaya students. The Nationalist Dimension consists of the values ​​of tolerance, adaptive, good character, and love for the country. The Patriotic Dimension consists ​​of being willing to sacrifice, obeying the rules, and being brave. While the Heroic Dimension consists of the values ​​of role models, responsibility, and achievement. The subjects in this study were 240 Unjaya students, consisting of 38 male students (15.8%) and 202 female students (84.2%). The results showed that Unjaya students had Nationalist (74%), Patriotic (72%), and Heroic (67%) levels included in the Moderate category (71%).